Ion transportation by Prussian blue nanoparticles embedded in a giant liposome. Issue 7 (23rd December 2019) - Uddin, S. M. Nizam; Laokroekkiat, Salinthip; Rashed, Md. A.; Mizuno, Shino; Ono, Kenta; Ishizaki, Manabu; Kanaizuka, Katsuhiko; Kurihara, Masato; Nagao, Yuki; Hamada, Tsutomu
Abstract : A new type of artificial giant liposome incorporating ion transport channels and using nanoparticles of metal organic frameworks was demonstrated. Abstract : A new type of artificial giant liposome incorporating ion transport channels and using nanoparticles of metal organic frameworks was demonstrated. The micropores of Prussian blue nanoparticles served as ion transport channels between the outer and inner phases of liposomes.